Behavioural reactions of three-spined sticklebacks to simulated risk of predation-Effects of predator distance and movement - Joacim Näslund; Leo Pettersson; Jörgen I Johnsson (Canadian Science Publishing, 2016)
The behavioural response of animals to predation risk commonly depends on the behaviour of potential predators. Here, we report an experiment investigating effects of predator model (a life-like wooden trout model) distance and movement on the behaviour of three-spined sticklebacks Gasterosteus aculeatus L. in a standardized experimental setting. When the predator model was immobile, the behaviour of the sticklebacks could, in general, not be clearly distinguished from a no-predator control treatment. When moving the predator 41 cm towards the stickleback, clear anti-predator behaviours were observed. However, behavioural expression depended on the distance to the predator. At the two farthest distances (approaching from 129 to 88 cm and from 170 to 129 cm), the sticklebacks approached the predator and spent little time freezing. At the two closest distances (approaching from 88 to 47 cm and from 47 to 6 cm), the sticklebacks increased the distance to the predator model and froze their movements. These results suggest that the closest-distance groups showed avoidance behaviour, whereas the farthest-distance groups instead appeared to start inspecting the potential predator. This provides evidence for conditional anti-predator behaviour and highlights the importance of considering distance to, and movement of predator models when interpreting data from standardized behavioural trials.